Students’ representations about quality education: a longitudinal study on nursing and management degrees - Cid, Marília (2013)
Characterizing the quality of education may involve the analysis of several variables, such as human resources, financial resources, teaching methodologies, personal and social development, and positive academic results. Nevertheless, all elements of the education system matter and may contribute to improve its quality. Ultimately, the success of an education system depends on the interaction of all elements. In order to study the representations of quality, a longitudinal research project is taking place in some higher education institutions of Alentejo region (Portugal). In this paper, the authors analyzed the relationship between scores on quality education representations of students from the Évora University and Beja and Portalegre Polytechnic Institutes, attending on nursing and management degrees. The analyses of the selected factors had shown human and institutional factors as the most important.